The Benefits and Costs of Highly Expansionary Monetary Policy - Rawdanowicz, Łukasz (OECD Economics Department Working Papers, 2013)
How far to go - and to remain - in the direction of highly expansionary monetary policy hinges on the balance of marginal benefits and costs of additional monetary easing and its expected evolution over time. This paper sketches a framework for assessing this balance and applies it to four OECD economic areas: the euro area, Japan, the United Kingdom and the United States. The effectiveness of further stimulus via quantitative easing or forward guidance in affecting asset prices, interest rates and credit flows will depend on the state of the economy and the functioning of financial markets. Marginal costs could rise due to excessive risk-taking; higher inflation expectations; higher likelihood of ever-greening; and higher risks of financial instability in the exit phase, especially when exit from monetary accommodation is close in time and signs of negative effects are already apparent. The balance of marginal benefits and costs is found to be different across the main OECD areas. In the United States, the case for additional stimulus is weakening, while the opposite is true for the euro area and Japan. In the United Kingdom, the assessment is less clear cut